Materials for Bioresorbable Radio Frequency Electronics. (17th May 2013) - Hwang, Suk‐Won; Huang, Xian; Seo, Jung‐Hun; Song, Jun‐Kyul; Kim, Stanley; Hage‐Ali, Sami; Chung, Hyun‐Joong; Tao, Hu; Omenetto, Fiorenzo G.; Ma, Zhenqiang; Rogers, John A.
<x xml:space="preserve">Abstract</x> Materials, device designs and manufacturing approaches are presented for classes of RF electronic components that are capable of complete dissolution in water or biofluids. All individual passive/active components as well as system‐level examples such as wireless RF energy harvesting circuits exploit active materials that are biocompatible. The results provide diverse building blocks for physically transient forms of electronics, of particular potential value in bioresorbable medical implants with wireless power transmission and communication capabilities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>